Unlocking Coban Binangun's Tourism Potential: Enhancing Village Hospitality with Plintahan Destination Branding Profile: Membuka Potensi Pariwisata Coban Binangun: Meningkatkan Keramahtamahan Desa dengan Profil Branding Destinasi Plintahan - Hatuwe, Razif Zulvikar; Bakta , Nabila Ayu; Rahmawati, Indah Agustinah; Putri, Adelia Kharisma; Wardani, Dwi Sukma; Dijaya, Rohman (Proceedings of The ICECRS, 2023)
The aim of this service is to increase Coban Binangun's tourism potential through an attractive destination branding profile that focuses on natural attractions, culture and village hospitality. Apart from that, this service also encourages local communities to contribute to tourism development by emphasizing their hospitality and active involvement in tourist services. This service method includes tourism potential studies, which include conducting comprehensive research on the natural and cultural potential of Coban Binangun as well as assessing attractions that can be included in the destination branding profile. The hospitality training provides training to local communities about tourism services, hospitality, and how to help tourists have a good experience. The result of this service is increased public awareness and understanding of the benefits of "Plintahan" destination branding, which forms a consistent and well-known identity by tourists. This dedication has the implication that with increased tourism, local communities become more aware of the preservation of nature and local culture. Highlight: Destination Branding: Developing a compelling brand profile for Coban Binangun focusing on natural beauty and cultural richness to attract tourists. Community Engagement: Encouraging local participation by training them in hospitality and tourist services, fostering their involvement in tourism development. Awareness and Conservation: Increased awareness among tourists and locals about the "Plintahan" brand, leading to a more profound understanding of the need for preserving nature and local culture. Keyword: Binangun Waterfall, Natural Tourism, Promotion